Penerapan Metode Vogel's Approximation Method (VAM) dalam Optimasi Biaya Distribusi Jasa Penyewaan PlayStation Portabel JapraPS - Marselo M. Masengi; Heru Sutejo; Muhamad Kurniawan; Ripan Wenda; Andi Muhammad A. I. H; Christian Renaldy L (CV Edujavare Publishing, 2026)
Distribution is an important aspect of the operational activities of a portable PlayStation rental business because it directly affects operational costs and the quality of customer service. JapraPS, as a portable PlayStation rental business, serves customers across several areas in Jayapura City, each with different distribution requirements. This study aims to optimize the distribution costs of JapraPS's portable PlayStation rental services using the Vogel's Approximation Method (VAM). The research data were obtained from JapraPS's portable PlayStation rental transaction records during the May 2026 period, which include supply, demand, and distribution cost data for each service area. The VAM method was employed to determine the distribution allocation that minimizes costs while satisfying all customer demands. The results indicate that the optimal distribution allocation is achieved by distributing 36 transactions from Bibsy Warehouse to the Kotaraja area, 27 transactions from JapraPS Warehouse to the Entrop area, 18 transactions from Bibsy Warehouse to the Jayapura area, and 28 transactions from JapraPS Warehouse to the Jayapura area. Based on the calculation results, the minimum total distribution cost obtained during the study period was IDR 4,190,000. These findings demonstrate that the Vogel's Approximation Method can be utilized as a decision-support tool to optimize the distribution of portable PlayStation rental services, thereby reducing operational costs more efficiently.